Reversal of 'the dying' diagnosis. Issue 6 (7th June 2021) - Ali, Maimoona; Goddard, Andrew; Smith, Eleanor
Abstract : A 75-year-old woman was admitted with sepsis and treated with broad-spectrum antibiotics until examination of her lower limbs noted necrotising wounds. Surgical intervention was advised by the plastic surgeons; however, she was deemed unsuitable for intensive care. She underwent incision and drainage of the necrotic area and biopsies were taken. She deteriorated clinically and the decision was made for best supportive care and was therefore transferred to the inpatient palliative care unit for end-of-life care. However, she stabilised, and based on culture sensitivities, antibiotics were restarted. It was also noted that the patient had a 3-month history of loose stools, which had not been addressed previously. The biopsies were suggestive of pyoderma gangrenosum, prompting a dermatology review, and prednisolone and doxycycline were started. The wounds and her loose stools improved, and with ongoing rehabilitation, she made a full recovery. Referral to gastroenterology was made.